“REHABILITATION OF PATIENTS WITH RESPIRATORY ORGANS” - Khamrayeva Zulayho Egamovna; Yakhyaev Kamol Saidovich; Annaqulova Saltanat Qarshibayevna (Western European Studies, 2025)
This review synthesizes current evidence on the effectiveness of respiratory rehabilitation across a range of respiratory disorders, including asthma, COPD, and lung infections. The core objectives of rehabilitation, encompassing improved respiratory function, increased physical activity, complication prevention, and enhanced quality of life, are examined through a critical analysis of existing literature. While considerable evidence supports the benefits of rehabilitation, significant gaps remain in understanding optimal strategies for diverse patient populations and tailoring interventions to individual needs. Future research should focus on [Areas for Future Research, e.g., identifying biomarkers predictive of response, developing personalized rehabilitation plans, evaluating cost-effectiveness]. This review emphasizes the importance of a multidisciplinary, patient-centered approach to respiratory rehabilitation to maximize positive outcomes.
Keywords: respiratory rehabilitation; lung function; dyspnea